Ultrasensitive photoelectrochemical immunosensor based on floral cluster SnS2/ZnCdS heterostructure for the detection of CA199 - Zhou, Hui; Guo, Qingqing; Zhang, Xin; Chu, Tingting; Zhang, Wen; Liu, Qing; Cao, Linlin (Frontiers in Bioengineering and Biotechnology, 2025)
The early and accurate detection of tumor markers is crucial for cancer diagnosis, prognosis, and treatment monitoring. Carbohydrate antigen 199 (CA199), as a key biomarker of pancreatic, gastric, and colorectal cancers, is widely used in the clinical management. The development of sensitive, rapid and cost-effective detection methods for CA199 is of paramount importance in improving early detection rates and patient outcomes. In this study, we present a novel photoelectrochemical (PEC) immunosensor based on a SnS2/ZnCdS heterostructure designed for the ultrasensitive detection of CA199. The unique heterojunction between SnS2 and ZnCdS enhances photocurrent generation by effectively suppressing charge recombination and improving charge separation. Furthermore, the flower-like morphology of the heterostructure further boosts light absorption and photogenerated carrier transport, resulting in significantly enhanced sensor performance. This label-free PEC immunosensor exhibits outstanding stability, reproducibility and selectivity, with a broad detection range from 0.01 to 1000 U/mL and an ultra-low detection limit of 1.00 × 10−3 U/mL. These features demonstrate the potential of this sensor as a powerful tool for sensitive CA199 detection, offering promising applications in cancer diagnostics and monitoring.